Evolution of Cold Tolerance Strategies in Insects - Gulevskiy, A. K.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2011)
The hypotheses on the problem of evolution of the main strategies of insects cold-hardiness are contemplated in the review. The present-day conceptions on the role of diapause in the development of insects cold-hardiness are described. The possible ways of origin of the main biochemical components of cold-hardiness, polyols and sugars, ice-nucleating and antifreeze proteins, are discussed.